2014
DOI: 10.3109/02713683.2014.968936
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of One-Piece and Three-Piece Tecnis Aspheric Intraocular Lenses: 1-year Stability and its Effect on Visual Function

Abstract: The stability of the one-piece IOL was greater than that of the three-piece IOL. The postoperative ACD and refractive error demonstrated that an anteriorly offset haptic in the one-piece IOL allowed incremental fixation to the posterior capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…The anteriorly offset haptics of the Tecnis lens enable a three-point fixation with the posterior capsule. According to Miyata et al [ 22 ], the one-piece Tecnis IOL showed a better stability than the three-piece IOL. They measured a mean postoperative ACD of 4.14 mm in eyes with mean AL of 23.37 mm twelve months after surgery with Scheimpflug camera, not including the corneal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The anteriorly offset haptics of the Tecnis lens enable a three-point fixation with the posterior capsule. According to Miyata et al [ 22 ], the one-piece Tecnis IOL showed a better stability than the three-piece IOL. They measured a mean postoperative ACD of 4.14 mm in eyes with mean AL of 23.37 mm twelve months after surgery with Scheimpflug camera, not including the corneal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The SE became more hyperopic significantly in the early Nd:YAG group compared with that in the late Nd:YAG group in the current study. In previous studies, the SE showed similar value after Nd:YAG laser capsulotomy whether in monofocal or multifocal IOL [21,24], and no related factors for the hyperopic or myopic change of SE were found except for the IOL design [19,20,25]. However, those studies did not consider the effect of Nd:YAG laser capsulotomy at different time periods, which may be a critical factor for the refraction since IOL stability is not consistent after the cataract surgery [22].…”
Section: Discussionmentioning
confidence: 93%
“…2015; Miyata et al. 2015). However, our results in Group B (three‐piece IOL in PXF eyes) did not show any significantly shallower depth value for ACD, although they indicated a slight myopia in comparison to Group A (one‐piece IOL in PXF eyes) and Group C (one‐piece IOL in non‐PXF eyes).…”
Section: Discussionmentioning
confidence: 99%